Comparative genomic analyses of Polymyxin-resistant Enterobacteriaceae strains from China - Zhien He; Yongqiang Yang; Wei Li; Xiaoling Ma; Changfeng Zhang; Jingxiang Zhang; Baolin Sun; Tao Ding; Guo-bao Tian (BMC Genomics, 2022)
Abstract Background Mobile colistin resistance like gene (mcr-like gene) is a new type of polymyxin resistance gene that can be horizontally transferred in the Enterobacteriaceae. This has brought great challenges to the treatment of multidrug-resistant Escherichia coli and K. pneumoniae. Results K. pneumoniae 16BU137 and E. coli 17MR471 were isolated from the bus and subway handrails in Guangzhou, China. K. pneumoniae 19PDR22 and KP20191015 were isolated from patients with urinary tract infection and severe pneumonia in Anhui, China. Sequence analysis indicated that the mcr-1.1 gene was present on the chromosome of E. coli 17MR471, and the gene was in the gene cassette containing pap2 and two copies of ISApl1.The mcr-1.1 was found in the putative IncX4 type plasmid p16BU137_mcr-1.1 of K. pneumoniae 16BU137, but ISApl1 was not found in its flanking sequence. Mcr-8 variants were found in the putative IncFIB/ IncFII plasmid pKP20191015_mcr-8 of K. pneumoniae KP20191015 and flanked by ISEcl1 and ISKpn26. Conclusion This study provides timely information on Enterobacteriaceae bacteria carrying mcr-like genes, and provides a reference for studying the spread of mcr-1 in China and globally.